Penerapan Model Pembelajaran Saintifik Approacd Berbasis Media Pembelajaran Kearifan Lokal pada Mata Kuliah Dasar-Dasar Sosiologi dalam Membangun Karakter dan Meningkatkan Hasil Belajar Mahasiswa Pendidikan Sosiologi Universitas Muhammadiyah Makassar - Suardi Suardi; syarifuddin syarifuddin (Universitas of Muhammadiyah Makassar, 2018)
The research objective is to analyze student activity during the learning process (ii) analyze student learning outcomes (iii) identify emerging character values (iv) identify obstacles that arise when applying the scientific approach learning model through learning media of local wisdom through classroom action research ( class room action research) for class A students in 2018. Student learning outcomes through the application of comparative scientific approach learning models in cycle I achieved classical completeness only reached 65.37% and in the second cycle had increased to 92.30% of the standard 90% completeness and reached KKM value 85. Student activity in the learning process in the first cycle was very high reaching 80.11 and cycle II which was 91.79 had reached the standard of 90%. Reflections on cycles I and II include the learning process using approacd scientific learning models, lecture contracts, dress rules, evaluation of learning, classroom use and publications on blogs so as to correct deficiencies of cycle I to cycle II. The results of the majority student questionnaire said (a) It was very pleasant with the application of the application of the scientific learning model approacd (b) Media classroom had grown the character of students' discipline and responsibility (c) Lecturers were very pleasant.Keywords: scientific approach, learning media, local wisdom, character